Pemulihan Ekonomi Keluarga UMKM Lokal melalui Pelatihan Desain Kemasan Produk dan Pemasaran Online di Desa Pekandangan Jaya, Kabupaten Indramayu - Ade Taryudi; Dzieky Maulana; Hafifah Hafifah; Junah Kistia; Nur Hanifah; Dwi Retno Hapsari (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Micro, Small and Medium Enterprises (MSMEs) are trading businesses managed by business entities or individuals. MSMEs in Pekandangan Jaya Village have difficulty in marketing products, looking for raw materials so that productivity is low. In overcoming these constraints, the objectives of the IPB Goes to Field (IGTF) 2020 program organized by the Institute for Development and Research to the Community (LPPM) of Bogor Agricultural University provide an opportunity to be able to help MSMEs solve the problem. SMART MSME program, which is implemented by empowering MSMEs and youth cadets through subprograms, namely the formation of UMKM Berkah Bersama group, Online Marketing Class, Product Packaging Graphic Design Training for MSMEs, and simple sales bookkeeping. In addition, the results of the SMART MSME program, namely the establishment of online marketing platforms (tokopedia and instagram), partners understand about design using graphic design applications, and packaging on partners successfully updated into products of higher selling value. Keywords: raw materials, digital marketing, training, micro small and medium enterprises.